Remediating doctors’ performance to restore patient safety: a realist review protocol - Price, T; Brennan, N; Cleland, J; Prescott-Clements, L; Wanner, A; Withers, L; Wong, G; Archer, J (BMJ Publishing Group, 2018)
Introduction: Underperformance by doctors poses a risk to patient safety. Remediation is an intervention designed to remedy underperformance and return a doctor to safe practice. Remediation is widely used across healthcare systems globally, and has clear implications for both patient safety and doctor retention. Yet, there is a poor evidence base to inform remediation programmes. In particular, there is a lack of understanding as to why and how a remedial intervention may work to change a doctor’s practice. The aim of this research is to identify why, how, in what contexts, for whom and to what extent remediation programmes for practising doctors work to support patient safety. Methods and analysis: Realist review is an approach to evidence synthesis that seeks to develop programme theories about how an intervention works to produce its effects. The initial search strategy will involve: database and grey literature searching, citation searching and contacting authors. The evidence search will be extended as the review progresses and becomes more focused on the development of specific aspects of the programme theory. The development of the programme theory will involve input from a stakeholder group consisting of professional experts in the remediation process and patient representatives. Evidence synthesis will use a realist logic of analysis to interrogate data in order to develop and refine the initial programme theory into a more definitive realist programme theory of how remediation works. The study will follow and be reported according to Realist And Meta-narrative Evidence Syntheses—Evolving Standards (RAMESES). Ethics and dissemination: Ethical approval is not required. Our dissemination strategy will include input from our stakeholder group. Customised outputs will be developed using the knowledge-to-action cycle framework, and will be targeted to: policy-makers; education providers and regulators, the National Health Service, doctors and academics. PROSPERO registration number CRD42018088779.